Sexual coercion in young persons: exploring the experiences in Ibadan, Nigeria (2004)
In-depth interviews with eight female victims of rape in Ibadan, Nigeria were used to explore the context in which the coercive incident occurred, the health-seeking behaviours that followed and the consequences of this experience in victims' lives. The mean age of the women was 17 years. In all cases, perpetrators of rape were persons with whom the women were acquainted. Rape occurred mainly in familiar and private settings. Rarely do victims communicate the incident to family or friends or report the incident to the enforcement authorities. The stigma associated with rape is a primary barrier to seeking care. Interventions are proposed to address these problems.